(untitled) (Scientific journal of the Fergana State University, 2023)
We know that our independent Uzbekistan went through its own obstacles to reach such happy days. The attitude of the people living in our country at the time of the overcome obstacles, their attitude towards the old system to the new system, their ideas at that time and their attitude towards the positive changes that happened later is one of the relevant conclusion processes even now. From this point of view, it is useful to think objectively about the changes taking place in the works of Togay Murad, the people’s writer of Uzbekistan. In the article, opinions and considerations are given on how Togay Murad’s works have gained a special place with their due importance in a time when the present is rapidly changing.